Self-Care and Quality of Life Among Adult Patients With Heart Failure: Scoping Review - Sheka Shemsi Seid MSc; José Amendoeira Post-PhD; Maria Regina Ferreira PhD (SAGE Publishing, 2023)
Introduction Although self-care has a therapeutic effect on heart failure (HF), patients experience a marked reduction in physical and executive function, resulting in poor quality of life (QoL). A literature review revealed limited evidence regarding the possible relationship between self-care and QoL in HF patients. Therefore, this scoping review aimed to identify scientific evidence that examines the extent of self-care, QoL, and relationship between self-care and QoL in patients with HF. Methods Full-text research published from March 23, 2010, to March 23, 2020, written in English, that had content on both self-care and QoL among adult patients with HF was included. A literature search of electronic databases and web searches was conducted for published articles. Four databases were used: MEDLINE, Scopus, Web of Science, and the Cochrane Library. Studies collected from Google and Google Scholar web searches were also included. Results Of 1,537 papers identified by the search, 12 were included. The reviewed studies included 3,127 patients. Ten articles used a cross-sectional study design, whereas the remaining articles used a longitudinal and quasi-experimental design. This review found that the extent of self-care practices among patients with HF was inadequate, a significant proportion of patients enrolled in the reviewed studies had a moderate QoL, and higher self-care practices were associated with a better QoL. Self-care behavior and QoL were affected by social support, sex, age, educational level, place of residence, illness knowledge, presence of comorbidities, and functional classification of HF. Conclusion Self-care behavior was positively correlated with QoL in patients with HF. Self-care and QoL in these patients have been reported to be affected by several factors. Further research with a rigorous study design is recommended to investigate the influence of self-care practices on QoL in patients with HF.